2014
DOI: 10.4238/2014.april.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the NPPB gene promoter c.-1298 G/T polymorphism site and pulse pressure in the Chinese Han population

Abstract: ABSTRACT. The aim of this study was to investigate the correlation between the natriuretic peptide precursor B (NPPB) gene single nucleotide polymorphism (SNP) c.-1298 G/T and pulse pressure (PP) of the Chinese Han population and the association between genotype and clinical indicators of hypertension. Peripheral blood was collected from 180 unrelated patients with hypertension and 540 healthy volunteers (control group), and DNA was extracted to amplify the 5'-flanking region and 2 exons of the NPPB gene by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Through binding with acetylated RelA, BRD4 enhances activation of NF-κB signaling to induce natriuretic peptide precursor A ( NPPA ) and natriuretic peptide precursor B ( NPPB ) transcription [ 24 ]. Our previous research also found that a SNP in the NPPB gene is associated with high PP [ 14 ]. BRD4 plays a critical role in propagating inflammation and promoting vascular calcification in particular [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Through binding with acetylated RelA, BRD4 enhances activation of NF-κB signaling to induce natriuretic peptide precursor A ( NPPA ) and natriuretic peptide precursor B ( NPPB ) transcription [ 24 ]. Our previous research also found that a SNP in the NPPB gene is associated with high PP [ 14 ]. BRD4 plays a critical role in propagating inflammation and promoting vascular calcification in particular [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…PCR amplification was carried out in a PTC-200 MJ Research Peltier Thermal Cycler (Bio-Rad Lab, Massachusetts, USA). Genotyping of the five examined SNPs was performed as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%